2010
DOI: 10.3414/me10-01-0038
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Health Records

Abstract: The manuscript gives comprehensive insight into the currently available, primarily non-functional, EHR requirements. To our knowledge, there are no other publications that have holistically reported on this topic. The requirements identified can be used in different ways, e.g. the conceptual design, the development of EHR systems, as a starting point for further refinement or as a basis for the development of specific sets of requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(17 citation statements)
references
References 94 publications
0
16
0
1
Order By: Relevance
“…Furthermore, in this study we have not considered any information from the patients' electronic health records (EHRs) [32], such as diagnoses or additional history. Considering the multi-factorial aetiology of falls [33], our sensor-based information may well be used in combination with resp.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in this study we have not considered any information from the patients' electronic health records (EHRs) [32], such as diagnoses or additional history. Considering the multi-factorial aetiology of falls [33], our sensor-based information may well be used in combination with resp.…”
Section: Discussionmentioning
confidence: 99%
“…4 There is evidence of significant potential for better quality and safety in health care deriving from the adoption of EHRs. 1,5,6 For example, in a study of 58 US hospitals over a 3 year period (2008-2011), EHR use was associated with 1.6% increase in overall health-care service productivity. 7 Another, nationally representative, study of physicians (n = 1727) in the USA reported great clinical benefits from EHRs.…”
Section: Introductionmentioning
confidence: 99%
“…These aspects will have direct impact in data redundancy, granularity, specification of mandatory fields and the existence of multiple feature values, which are directly linked with challenges 3, 4 and 5 of this article. Secondly, training of health professionals in using EHR systems is crucial to determine the format and quality of routinely collected data, coupled with in embedded validation mechanisms [77]. As such, we call attention to the importance of creating awareness of the implications of EHR design and use to the reuse of clinical data, namely by providing proper training and feedback, ultimately aiming for continuous improvement [78].…”
Section: Discussionmentioning
confidence: 99%